Preschool Internship with Johnson Ferry Baptist Church - Jackson, Rebekah (My University, 2018)
After 12 weeks of working with over 1,000 kids, anyone is guaranteed to learn some lessons. My internship with Johnson Ferry Baptist Church in Atlanta, Georgia provided an opportunity for me to apply many concepts I learned in class. I learned about the important role of fun in learning, about the delicate balance of classroom management, about how to create meaningful educational interactions with kids, about writing, publishing and using curriculum, and many other ways to apply classroom material. I realized what a wide variety of applications a major in Education provides, even outside of traditional classrooms!